2002
DOI: 10.3109/s101650200039
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms associated with enteric-coated sulfasalazine (Azulfidine EN tablets)

Abstract: To investigate both the incidence and the dosage used to treat gastrointestinal (GI) symptoms associated with enteric-coated sulfasalazine (Azulfidine EN, AZL) in patients with rheumatoid arthritis (RA), we studied the clinical history of 153 RA patients, and any available data on GI symptoms that might have been associated with AZL. GI symptoms appeared in 64 (42.5%) of the 153 cases. There were 19 events of nausea, vomiting, or dyspepsia, 14 events each of epigastric discomfort and reduction or loss of appet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…2 Similarly, we find that sulfasalazine (a drug used to treat rheumatoid arthritis and ulcerative) causes vomiting. This finding is supported by [41], which reports that 64 out of 152 people developed adverse reactions due to this drug, and 19 out of that 64 had vomiting. Finally, our model predicts halcinonide to cause hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…2 Similarly, we find that sulfasalazine (a drug used to treat rheumatoid arthritis and ulcerative) causes vomiting. This finding is supported by [41], which reports that 64 out of 152 people developed adverse reactions due to this drug, and 19 out of that 64 had vomiting. Finally, our model predicts halcinonide to cause hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…A total of 62 cases of pruritus were reported, with incidences of pruritus in RA patients varying from 0.8% ('uncommon') to 25.0% ('very common'). Mucositis (including mouth ulceration and stomatitis) associated with the use of sulfasalazine is mentioned with an incidence 'unknown' in the SmPC, but is a well-known ADR in literature [35]. A retrospective study of Okubo et al [2002, 35] reported an estimated incidence of 5.9% (n = 9), implying the incidence is 'common'.…”
Section: Discussionmentioning
confidence: 99%
“…They resolve with discontinuation or dose reduction and are better tolerated with the use of an enteric-coated formulation. 87,88…”
Section: Sulfasalazinementioning
confidence: 99%